1986
DOI: 10.1002/bjs.1800730223
|View full text |Cite
|
Sign up to set email alerts
|

Resection and colo-anal anastomosis with colonic reservoir for rectal carcinoma

Abstract: Sphincter-saving operations are now generally accepted for the treatment of mid-rectal cancers. Many techniques have been described: low colorectal anastomosis, pull-through procedures, and colo-anal anastomosis. The functional results following these operations are impaired by loss of the reservoir function of the rectum. In order to improve these results, a modification of Parks' colo-anal anastomosis is proposed. A J-shaped colic reservoir is constructed and its end is anastomosed to the anal canal. We have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
152
0
21

Year Published

1990
1990
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 395 publications
(173 citation statements)
references
References 11 publications
0
152
0
21
Order By: Relevance
“…Такие негативные изменения в раннем и отдаленном послеоперационном периоде не позволяли считать ре-зультаты лечения больных раком прямой кишки удовлет-ворительными, даже не смотря на хорошие отдаленные результаты в выживаемости. На протяжении длительного времени, а особенно с на-чала-середины 2000-х годов, хирурги, онкологи-коло-проктологи искали различные варианты в лечении, чтобы улучшить функциональные результаты после резекций прямой кишки, не в ущерб принципам онкологического радикализма [3,5,6,8,9,16,17] • №1 -2016 г. (17) • www.malignanttumours.org в 1986 году были опубликованы первые работы по форми-рованию J-образного анастомоза (F. Lazorthes и R. Parc).…”
Section: инновационная малоинвазивная колопроктологияunclassified
“…Такие негативные изменения в раннем и отдаленном послеоперационном периоде не позволяли считать ре-зультаты лечения больных раком прямой кишки удовлет-ворительными, даже не смотря на хорошие отдаленные результаты в выживаемости. На протяжении длительного времени, а особенно с на-чала-середины 2000-х годов, хирурги, онкологи-коло-проктологи искали различные варианты в лечении, чтобы улучшить функциональные результаты после резекций прямой кишки, не в ущерб принципам онкологического радикализма [3,5,6,8,9,16,17] • №1 -2016 г. (17) • www.malignanttumours.org в 1986 году были опубликованы первые работы по форми-рованию J-образного анастомоза (F. Lazorthes и R. Parc).…”
Section: инновационная малоинвазивная колопроктологияunclassified
“…Building on successful experience with the ileoanal pouch in familial adenomatous polyposis and ulcerative colitis following proctocolectomy, the colonic J pouch was introduced by Lazorthes and Parc (26,125) The clinical results and manometric data have been compared with straight colorectal and coloanal anastomosis in controlled studies, including numerous randomized trials (29,33,41,54,56,63,88,100,122,123,143,146). According to a meta-analysis (49), the CJP has unique advantages compared with straight coloanal anastomosis: Bowel movement was significantly less up to 2 years after surgery, significantly fewer patients suffered from an imperative urge to defecate up to one year post-operatively and significantly fewer patients had to take antidiarrheals.…”
Section: Colon J Pouch (Cjp)mentioning
confidence: 99%
“…Evacuation disturbances were observed in up to 60 % of patients when the colon J pouch was first introduced into clinical practice (11,4354,113,125,130), and this increased the more time passed after the operation (88) The evacuation disorders were attributed to an overlong pouch, since such disorders occurred in particularly high numbers when the pouch was longer than 8 cm (11, 41,113,125,130). Randomized trials with different lengths of pouch then showed a tendency to, or a significantly higher rate of evacuation disorders when the pouch was 10 cm long (30,87).…”
Section: Length Of Pouchmentioning
confidence: 99%
“…Lazorthes et al (3) e Parc et al (4) propuseram simultaneamente em 1986 o emprego do reservatório colônico após ressecções retais baixas no sentido de melhorar os resultados funcionais no pós-operatório imediato. Pelissier et al (5),em 1992, realizaram a operação utilizando exclusivamente sutura mecânica, com o propósito de diminuir a contaminação intra-operatória.…”
Section: Introductionunclassified